BLENDED LEARNING: STUDENT PERCEPTION OF FACE-TO-FACE AND ONLINE EFL LESSONS - Wright, Brenda M. (Indonesian Journal of Applied Linguistics, 2017)
With the ever-increasing development of technology, online teaching is more readily accepted as a viable component in teaching and learning, and blended learning, the combining of online and face-to-face learning, is becoming commonplace in many higher education institutions. Blended learning is, particularly in developing countries, in its early stages and not without its challenges. Asynchronous online lessons are currently still more prevalent in many areas of South-East Asia, perhaps due to potential difficulty in obtaining strong Internet connections, which may deter educators from synchronous options. Technological media have the potential to broaden the scope of resources available in teaching and to enhance the language learning experience. Although research to date shows some focus on blended learning, literature on distance online teaching seems more prevalent. This study exposed 112 Malaysian undergraduate EFL students' responses to an online lesson as part of an English grammar course, and investigates common student perceptions of the online lesson as compared with face-to-face lessons. Questionnaires using qualitative (Likert scale questions) and quantitative (open-ended questions) approaches provided data for content analysis to determine common student perceptions, with particular reference to motivation and interest. In general, more students associated in-class lessons with higher motivation and more interest, due to better understanding, valued classroom interaction with the lecturer and peers, and input from the lecturer. Students preferring the online lesson cited speed and convenience of study and flexibility of time and place of study as reasons for their choice. Skilful implementation of online lessons can enhance a language course but should not undermine the value of face-to-face instruction with EFL teachers.